Moody Mares—Is Ovariectomy a Solution? - Daniel Taasti Melgaard; Trine Stokbro Korsgaard; Martin Soendergaard Thoefner; Morten Roenn Petersen; Hanne Gervi Pedersen (Animals, 2020)
Unwanted behaviour in mares is a commonly presenting problem to the veterinarian. This behaviour may range from the mare being uncooperative or aggressive when handled on the ground, kicking, bucking or rearing when ridden or being aggressive towards other horses. This purpose of the study was to evaluate whether bilateral ovariectomy in mares with unwanted behaviour improved the mare’s behaviour and/or rideability from the owner’s perspective. The mares were grouped and compared statistically based on their histological classification as having either “normal” or neoplastic ovaries. This study is a retrospective case series report of twenty-eight ovariectomized mares. A semi-quantitative value (1–10) pre- and post-ovariectomy for A) behaviour on ground/in stable and B) rideability was given, based on the owner’s observations. The horses were grouped based on their histopathologic diagnosis as “Normal ovaries” or “Neoplasia”. Following ovariectomy, rideability improved, with a score of ≥5 in 80% (8/10) of mares with normal ovaries and in 57% (8/14) of mares with ovarian neoplasm. A behavioural improvement of ≥5 was observed in 40% (4/10) of mares with normal ovaries, and in 43% (6/14) of mares with ovarian neoplasm. A significant difference was observed between the semi-quantitative value pre- and post-ovariectomy in both groups. No difference was observed in change in behaviour and rideability score between the group with normal ovaries and neoplastic ovaries. Mares with unwanted behaviour not obviously related to the oestrus cycle and to painful conditions may benefit from ovariectomy to alter their behaviour and rideability.